Early Stimulation in the Psychological Development of Early Childhood: A Comprehensive Literature Review - Amanah Rahma Ningtyas; Idi Warsah; H. M. Taufik Amrillah; Epni Lidya Utami (Jurnal Caksana : Pendidikan Anak Usia Dini, 2026)
This study aims to explain early detection in the psychological development of early childhood. Psychological development during early childhood serves as a critical foundation for character formation, learning abilities, and future social relationships. This research employs a library research approach with stages including scientific review, theoretical study of all research objects, and theoretical analysis. The study is expected to assist parents and educators in understanding various theories addressing early detection of psychological development in early childhood. The findings indicate that theoretically, there are two main conclusions: first, early childhood developmental psychology is the science studying mental, physical, cognitive, linguistic, moral, and socio-emotional development; second, early detection is essential in monitoring psychological development during early childhood. The study emphasizes that early childhood represents a golden period wherein rapid development occurs across all domains, making it imperative for parents and educators to understand developmental milestones and potential deviations. Early detection enables timely intervention, preventing more severe developmental challenges. The synergy between family, school, and community environments plays a pivotal role in supporting optimal psychological growth. This paper underscores the importance of understanding early childhood developmental psychology as a foundation for improving the quality of education and childcare in Indonesia. Furthermore, the study highlights that psychological development is influenced by both innate factors and environmental stimulation, necessitating a holistic approach to early childhood education that integrates cognitive, linguistic, socio-emotional, moral, and motor development proportionally.